Essential Oil of Common Sage (Salvia officinalis L.) from Jordan: Assessment of Safety in Mammalian Cells and Its Antifungal and Anti-Inflammatory Potential. (9th October 2013) - Abu-Darwish, M. S.; Cabral, C.; Ferreira, I. V.; Gonçalves, M. J.; Cavaleiro, C.; Cruz, M. T.; Al-bdour, T. H.; Salgueiro, L.
Abstract : Salvia officinalis L. (Lamiaceae) is a Mediterranean species, naturalized in many countries. In Jordan, it is used in traditional medicine as antiseptic, antiscabies, antisyphilitic, and anti-inflammatory, being frequently used against skin diseases. This study aimed the assessment of the antifungal and anti-inflammatory potential of its essential oils, and their cytotoxicity on macrophages and keratinocytes. The oils were investigated by gas chromatography and gas chromatography-mass spectrometry and the antifungal activity was evaluated against yeasts, dermatophyte and Aspergillus strains. Assessment of cell viability was made by the 3-(4, 5-dimethylthiazol-2-yl)-2, 5-diphenyltetrazolium bromide assay and the in vitro anti-inflammatory potential was evaluated by measuring nitric oxide production using lipopolysaccharide-stimulated mouse macrophages. The main compounds of S. officinalis oils were 1, 8-cineole (39.5–50.3%) and camphor (8.8–25.0%). The oils revealed antifungal activity against dermatophyte strains and significantly inhibited NO production stimulated by LPS in macrophages, without affecting cell viability, in concentrations up to 0.64  μ L/mL. This is the first report addressing the in vitro anti-inflammatory potential of S. officinalis oil. These findings demonstrated that bioactive concentrations of S. officinalis oils do not affect mammalian macrophages and keratinocytes viability making them suitable to be incorporated in skin care formulations for cosmetic and pharmaceutical purposes.